First Molecular Evidence for Puumala Hantavirus in Poland - Hanan Ali; Stephan Drewes; Edyta Sadowska; Magdalena Mikowska; Martin Groschup; Gerald Heckel; Pawel Koteja; Rainer Ulrich (Viruses, 2014)
Puumala virus (PUUV) causes mild to moderate cases of haemorrhagic fever with renal syndrome (HFRS), and is responsible for the majority of hantavirus infections of humans in Fennoscandia, Central and Western Europe. Although there are relatively many PUUV sequences available from different European countries, little is known about the presence of this virus in Poland. During population studies in 2009 a total of 45 bank voles were trapped at three sites in north-eastern Poland, namely islands on Dejguny and Dobskie Lakes and in a forest near Mikołajki. S and M segment-specific RT-PCR assays detected PUUV RNA in three animals from the Mikołajki site. The obtained partial S and M segment sequences demonstrated the highest similarity to the corresponding segments of a PUUV strain from Latvia. Analysis of chest cavity fluid samples by IgG ELISA using a yeast-expressed PUUV nucleocapsid protein resulted in the detection of two seropositive samples, both being also RT-PCR positive. Interestingly, at the trapping site in Mikołajki PUUV-positive bank voles belong to the Carpathian and Eastern genetic lineages within this species. In conclusion, we herein present the first molecular evidence for PUUV in the rodent reservoir from Poland.